Long-Term Minimum 15-Year Follow Up After Lateral Discoid Meniscal Preservation Surgery in Children and Adolescents. Issue 5 (31st May 2022) - Lins, Laura A.B.; Feroe, Aliya G.; Yang, Brian; Williams, Kathryn A.; Kocher, Sophia D.; Sankarankutty, Saritha; Micheli, Lyle J.; Kocher, Mininder S.
Background: Discoid meniscus is a congenital variant typically affecting the lateral meniscus of the knee. Historically, surgical intervention when symptomatic consisted of total meniscectomy; however, after degenerative changes were observed, current treatments now focus on rim preservation with arthroscopic saucerization and meniscal repair for instability, when indicated. Purpose: The aim of this study was to examine long-term patient-reported outcomes of lateral discoid menisci (LDM) treated with meniscal-preserving techniques. Methods: Ninety-eight patients treated arthroscopically for LDM at a single institution at a minimum of 15 years ago were retrospectively identified and contacted by mailers and telephone to participate. Subjective functional outcomes and patient satisfaction data were collected using a questionnaire that included the validated IKDC Subjective Knee Evaluation Form, Lysholm Score, Marx Activity Rating Scale, Tegner Activity Score, and WOMAC Osteoarthritis Index. Patient and surgical characteristics and patient-reported outcomes were summarized by mean and standard deviation (SD), median and interquartile range (IQR), or frequency and percent, as appropriate. Results: Of the 46 patients contacted (response rate of 46/98 eligible), 25 (54%) completed the questionnaires. The mean (± SD) age at initial surgery was 10.8 (± 3.4) years and 30.3 (± 3.7) years at final follow-up. The mean (± SD) follow-up time from initial surgery was 19.5 (± 2.8) years (range, 16–27). Patient-reported outcomes included: IKDC 77.4 ± 17.2, Lysholm 78.6 ± 21, WOMAC 7.6 ± 11.3, Tegner Activity 7 (out of 10), and Marx Activity Rating Scale 8 (out of 10) (Table 1). Eleven (44%) cases underwent subsequent LDM-related surgery on the ipsilateral knee(s). There were no cases of total knee replacement (Table 2). Conclusions: Overall, patient-reported outcomes were favorable at a minimum of 15-year follow-up after rim-preserving saucerization of lateral discoid meniscus. While two-thirds of patients were satisfied with their surgical outcomes, nearly half of patients underwent revision saucerization with or without meniscal repair. Subsequent long-term follow-up studies with radiographs will be important to determine how meniscus-preserving procedures may curb the development of arthritis. Table 1. Overall Postoperative Outcomes (N=25 patients) a Table 2. Postoperative Outcomes by Discoid Type and Surgery (N=26) a